Policy zero role illusion or reality in territorial entities (2019)
In the development of this document, an argumentative analytical work is carried out since zero-role public policy information will be taken on its importance in the territorial entities of the country and the analysis presented on its implementation, or on the contrary it is an illusion that does not may be brought to reality as long as territorial governments do not take measures to promote, monitor and control the inefficient consumption of paper and little promotion of culture over its use in public administration, together with the previous ones to the non-contribution of the austerity principle and the increase of operating expenses in the budgets of the entities, the lack of stimulus and non-use of the technological tools that currently have public administration that seek to contribute to the management of time and administrative efficiency therefore arises Question: DOES THE ZERO POLICY PAPERS ILLUSION OR REALITY IN THE TERRITORIAL ENTITIES?